1973
DOI: 10.1121/1.1914345
|View full text |Cite
|
Sign up to set email alerts
|

Masking produced by sinusoids of slowly changing frequency

Abstract: A fixed amplitude sinusoid that was frequency modulated by a sawtooth or triangle wave was used to mask a 20-msec pure-tone signal. The linear portions of the modulating waveforms were 150 msec in duration and swept the masker frequency between 1.5 and 0.75 kHz. A frequency contour of the masking was obtained when the temporal position of the signal was fixed relative to the sawtooth or triangle and the signal frequency was varied. A temporal contour of the masking was measured when the signal frequency was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The correlation analysis (Chapter 5) results showed higher correlations between human ratings and simulated observers, when a true integrator, or a leaky integrator with a very long time constant, was used. This is consistent with the findings of Makita and Miyatani (1950) and Henning and Psotka (1969), but not consistent with studies supporting leaky integration with a short time constant (Jeffress, 1967(Jeffress, , 1968Robinson & Pollack, 1973;Robinson, 1974;Ronken, 1973).…”
Section: Integration Time and Time Constantsupporting
confidence: 88%
See 1 more Smart Citation
“…The correlation analysis (Chapter 5) results showed higher correlations between human ratings and simulated observers, when a true integrator, or a leaky integrator with a very long time constant, was used. This is consistent with the findings of Makita and Miyatani (1950) and Henning and Psotka (1969), but not consistent with studies supporting leaky integration with a short time constant (Jeffress, 1967(Jeffress, , 1968Robinson & Pollack, 1973;Robinson, 1974;Ronken, 1973).…”
Section: Integration Time and Time Constantsupporting
confidence: 88%
“…Studies that have found evidence that the time constant of the temporal integrator was short include Robinson and Pollack (1973), Robinson (1974), andRonken (1973). Studies that have found long duration (greater than 200 ms) time constants include Makita and Miyatani (1950) and Henning and Psotka (1969).…”
Section: Experimental Estimations Of the Temporal Integratormentioning
confidence: 99%
“…In order to generate quantitative predictions, two free parameters of the model, the time constant of the integrator and the amplitude response of the auditory filter, had to be estimated from steadystate masking data. The present analysis employed a 16-msec time constant, which is in accord with a number of other psycho-acoustic results (Ronken, 1973). The off-band attenuation rate of the auditory filter was estimated directly from the masking pattern obtained in the continuous masker condition.…”
Section: Tion (Dashed Curve) Is Intermediate Between the Gated And Comentioning
confidence: 98%
“…3) Some authors reported the masking time pattern using periodically -frequency-modulated tones as maskers, where the test tone bursts were short enough to enable their insertion at distinct temporal locations within the masker's period. [4][5][6] This type of masking is called the masking period pattern. However, there are few studies on the masking for tones as maskers with transient frequency change.…”
Section: Introductionmentioning
confidence: 99%